Degradation of the beta-alumina electrolyte in a zebra cell - Van Heerden, D P (Centre for Materials Engineering, 2024)
Beta-alumina solid electrolytes studied were subjected to charge and discharge cycles in a secondary, high energy density Na/beta-al~mina/NaA1Cl 4/FeC1 2 cell (known as the Zebra cell) at 250 c. These electrolytes were studied by means of optical microscopy, as well as SEM and EDS analyses to establish possible failure modes. After cycling little discolouration, or impurity pickup was found to have occurred in the electrolyte. The forms of degradation of the beta-alumina electrolyte identified appeared to be a result of inherent flaws in the betaalumina electrolyte tube, problems due to protracted storage of the tubes, or an apparent interfacial film on the cathode/electrolyte interface. A lead wetting agent was used in the cells to enhance the wetting of the beta-alumina electrolyte by the liquid Na. A study of the this coating after cycling of the cell showed that the coating was adherent irrespective of the number of cycles completed. The coating did not appear to influence cracking of the electrolyte during cycling. Cracking of the beta-alumina electrolyte was found to have initiated from the Na/electrolyte interface. No evidence of crack initiation nor internal damage was found on the cathode/electrolyte interfac~. The cracks through the beta-alumina electrolyte wall were found to have sealed by the formation of a plug consisting largely of Na and Cl. on the basis of EDS analyses of the fracture surface of the sealed crack possible sealing mechanisms are proposed.